问题 解答题
观察下列等式:
1
2
+1
=
2
-1
(
2
+1)(
2
-1)
=-1+
2

1
3
+
2
=
3
-
2
(
3
+
2
)(
3
-
2
)
=-
2
+
3

1
4
+
3
=
4
-
3
(
4
+
3
)(
4
-
3
)
=-
3
+
4
;…
从计算结果中寻找规律,并利用这一规律计算:(
1
2
+1
+
1
3
+
2
+
1
4
+
3
+…+
1
2002
+
2001
)(
2002
+1)
答案

1
2
+1
=
2
-1
(
2
+1)(
2
-1)
=-1+
2

1
3
+
2
=
3
-
2
(
3
+
2
)(
3
-
2
)
=-
2
+
3

1
4
+
3
=
4
-
3
(
4
+
3
)(
4
-
3
)
=-
3
+
4
,…

(

1
2
+1
+
1
3
+
2
+
1
4
+
3
+…+
1
2002
+
2001
)(
2002
+1)

=[(-1+

2
)+(-
2
+
3
)+(-
3
+
4
)+…+(-
2001
+
2002
)](
2002
+1)

=(-1+

2
-
2
+
3
-
3
+
4
+…-
2001
+
2002
)(
2002
+1)

=(-1+

2002
)(
2002
+1

=(

2002
)2-12

=2002-1

=2001.

判断题
单项选择题